Parametric study of the minimum required reinforcement for cracking control in thick restrained RC members based on thermo-hygro-mechanical FE analyses - Sousa, Carlos (2018)
This paper discusses the structural behaviour of walls or slab-like reinforced concrete (RC) elements fully restrained at their ends, considering the effects of self-induced deformations due to the heat of hydration and concrete shrinkage. It focuses on the formation and propagation of cracks in thick ties. The analysed thicknesses are 500 mm and 1000 mm. The ultimate objective of the analyses presented in the paper is the rational calculation of the minimum required area of reinforcement to control cracking. For that purpose, thermo-hygromechanical analyses are conducted, so that the non-uniform cross-sectional distribution of self-induced deformations is conveniently simulated, and the crack propagation process can be studied. A staggered analysis approach is followed: an uncoupled thermo-hygral analysis is firstly conducted to calculate the self-induced deformation, in each location throughout the structure thickness, for each instant of time. Then, this deformation field is used as input for the mechanical analysis, where the relevant features of the mechanical concrete behaviour are simulated: maturity; creep; softening behaviour after cracking; and nonlinear bond stress-slip relationship at the steel-concrete interface. The results are discussed in view of the regulatory framework of Eurocode 2 for minimum reinforcement for adequate crack width control.